EFFECTIVENESS OF COMPREHENSIVE PREVENTIVE MEASURES IN REDUCING CARDIOVASCULAR RISK IN PATIENTS WITH DIABETES - Barakayeva Nigina O’tkir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines the effectiveness of comprehensive preventive strategies in lowering cardiovascular risk among patients with diabetes. Multifactorial interventions, including glycemic control, blood pressure management, lipid regulation, lifestyle modifications, and pharmacological therapy, significantly reduce the incidence of cardiovascular events. Early implementation of combined preventive measures improves patient outcomes and decreases morbidity and mortality associated with cardiovascular disease in diabetic populations.